Flap‐induced astigmatism in eyes with sphere myopia correction: Superior hinge using a rotating microkeratome versus nasal hinge using a linear microkeratome. Issue 6 (June 2015) - Katz, Toam; Frings, Andreas; Richard, Gisbert; Steinberg, Johannes; Druchkiv, Vasyl; Linke, Stephan J.
Abstract : Purpose : To compare the effect of a rotating microkeratome (M2) and a linear microkeratome (SBK) on the change in the astigmatic component in eyes with preoperative plano refractive cylinder. Setting : University Medical Centre Hamburg‐Eppendorf, Hamburg, Germany. Design : Retrospective case series. Methods : An Allegretto excimer laser was used to perform laser ablation in myopic eyes of consecutive patients. The laser in situ keratomileusis (LASIK) procedure included mechanical flap preparation using a microkeratome, either a linear type with a single‐use 90 μm head to create a nasal hinge or a rotating type with a single‐use 90 μm head to create a superior hinge. The Alpins vector method was applied to describe the effects of LASIK on postoperative refractive cylinder. Results : The study evaluated 1045 eyes of 852 patients. Although the mean overall efficacy and safety indices indicate the procedure was highly precise, safe, and efficient, there were statistically significant differences in surgically induced astigmatism (SIA) between the microkeratomes ( P = .002). The postoperative refractive cylinder (ie, SIA) was 0.75 diopter (D) or more in 116 eyes (11.1%), 44 (12.8%) of 344 linear cases and 72 (10.3%) of 701 rotating cases. Independent of the type of microkeratome used, the SIA was slightly higher in eyes treated first; the mean magnitude of the induced astigmatism was 0.35 D. Conclusions : In approximately 10% of eyes with preoperative plano refractive myopia, the astigmatic component tended to be overcorrected. Nevertheless, independent of the type of microkeratome, the maximum mean magnitude of refractive cylinder documented was 0.35 D. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.